Empowering customers: portals, supply networks and assemblers. (1st January 2002) - Spring, Martin; Sweeting, Robert C.
This paper synthesises a number of existing and emerging themes in the management of operations, supply networks, information and customer relationships. The model proposed here is one where the customer is in a position to dictate the form, delivery and price of the product or service required. Using primarily manufacturing concepts and examples, the paper outlines how this transformation may take place. The key elements considered are modular design of products and services, the widespread use of ERP, changing supply relationships and the potential of the internet. All these building blocks exist at present and the paper shows how a changed architecture, combined with the types of changes in customer expectations engendered and revealed by developments in e-commerce, will drive this transformation forward.